Kekerasan dalam Rumah Tangga (KDRT) yang Terjadi di Kota Bitung - Adam, Rahmat S.; Mallo, Nola T. S.; Tomuka, Djemi (Universitas Sam Ratulangi, 2024)
Abstract: According to the Ministry of Women's Empowerment and Child Protection (PPPA) through the Online Information System for the Protection of Women and Children (SIMFONI PPA), in North Sulawesi 2023, the most dominant violence based on the location of the incidence is household. Bitung is the area with the second highest number of domestic violence cases in 2023. This study aimed to obtain the description of domestic violence cases in Bitung 2022. This was a retrospective and descriptive study using secondary data taken from the Women's Empowerment and Child Protection Service and Police Department in Bitung. The relationships between variables were analayzed with the chi-square test. The results showed that the majority of victims were children (74.5%) with the type of penance violence (45.8%). Most often the perpetrator was the father (38.2%). The chi-square test obtained p=0.008 for the relationship between victim and all types of violence; p=0,000 for the relationship between the relation of perpetrator and victim and all types of violence; and p=0.542 for the relationship between location and all types of violence. In conclusion, the majority of domestic violence in Bitung is penance violence with children as the victims, and the father as perpetrator. There is no relationship between location and all types of violence. Keywords: types of violence; domestic violence; victim Abstrak: Kementerian Pemberdayaan Perempuan dan Perlindungan Anak (PPPA) melalui Sistem Informasi Online Perlindungan Perempuan dan Anak (SIMFONI PPA) melaporkan bahwa di Sulawesi Utara pada korban kekerasan per tahun 2023 yang paling mendominasi berdasarkan tempat kejadian ialah rumah tangga. Kota Bitung merupakan daerah dengan posisi ke-2 kasus kekerasan per tahun 2023. Penelitian ini bertujuan untuk menganalisis kasus KDRT di Kota Bitung. Jenis penelitian ialah deskrptif restrospektif dengan menggunakan data sekunder diambil dari Dinas Pemberdayaan Perempuan dan Perlindungan Anak Kota Bitung serta Polisi Resort Kota Bitung tahun 2022. Uji statistik terhadap hubungan variabel menggunakan uji chi-square. Hasil penelitian mendapatkan bahwa mayoritas korban ialah kategori anak (74,5%) dengan jenis kekerasan penelantaran (45,8%) serta pelaku paling banyak ialah ayah (38,2%). Hasil uji chi-square mendapatkan nilai p=0,008 pada variabel korban dengan semua jenis kekerasan; p=0,000 pada variabel hubungan pelaku dengan korban terhadap semua jenis kekerasan; dan p=0,542 pada hubungan antara variabel kecamatan dengan semua jenis kekerasan. Simpulan penelitian ini ialah mayoritas kekerasan dalam rumah tangga yang terjadi di Kota Bitung ialah penelantaran dengan korban terbanyak ialah anak, pelaku yang berstatus ayah, namun hubungan wilayah kejadian dari setiap kasus tidak berkontribusi dalam terjadinya kekerasan dalam rumah tangga. Kata kunci: jenis kekerasan; kekerasan dalam rumah tangga; korban